Effectiveness of a computerized cognitive training program for reducing head impact kinematics in youth ice hockey players - DiFabio, M. S.; Buckley, T. A. (International Journal of Exercise Science, 2021)
Cognitive training (CT) is an effective technique to improve neurological performance, but has not been investigated as a head impact primary prevention strategy. The purpose of this study was to investigate the CT`s effectiveness in reducing head impact kinematics in youth ice hockey players. Twenty youth were divided into two groups: a CT and Control group. The CT group performed two 30-minute sessions of IntelliGym CT weekly for 20 weeks and the control group performed two 30-minute sessions weekly evaluating hockey videos. The dependent variables, number of head impacts, cumulative linear acceleration (CLA) and rotational acceleration (CRA) and mean linear and rotation peak acceleration, were compared with repeated measures ANOVAs, with post-hoc for main effect of time for each group, between the first and second half of the season. There were significant interactions for number of head impacts (p = 0.014) and CLA (p = 0.043) and post-hoc testing identified reductions in the second half of the season for the CT, but not control, group. There were no interactions for CRA, mean peak linear acceleration, and mean peak rotational acceleration. These preliminary results suggest CT may be an effective primary prevention strategy to reduce head impacts and cumulative linear acceleration in youth ice hockey players.